Casitas: a location-dependent ecological trap for juvenile Caribbean spiny lobsters, Panulirus argus. (15th March 2015) - Gutzler, Benjamin C.; Butler, Mark J.; Behringer, Donald C.
Abstract: Casitas are artificial shelters used by fishers to aggregate Caribbean spiny lobsters ( Panulirus argus ) for ease of capture. However, casitas may function as an ecological trap for juvenile lobsters if they are attracted to casitas and their growth or mortality is poorer compared with natural shelters. We hypothesized that juvenile lobsters may be at particular risk if attracted to casitas because they are less able than larger individuals to defend themselves, and do not forage far from shelter. We compared the nutritional condition, relative mortality, and activity of lobsters of various sizes in casitas and natural shelters in adult and juvenile lobster-dominated habitats in the Florida Keys (United States). We found that the ecological effects of casitas are complex and location-dependent. Lobsters collected from casitas and natural shelters did not differ in nutritional condition. However, juvenile lobsters in casitas experienced higher rates of mortality than did individuals in natural shelters; the mortality of large lobsters did not differ between casitas and natural shelters. Thus, casitas only function as ecological traps when deployed in nursery habitats where juvenile lobsters are lured by conspecifics to casitas where their risk of predation is higher. These results highlight the importance of accounting for animal size and location-dependent effects when considering the consequences of habitat modification for fisheries enhancement.